L'élevage camelin en Tunisie - Moslam M.; Megdiche F. (Séminaire sur la digestion, la nutrition et l'alimentation du dromadaire, 1989)
Used as a draught animal and for transportation, camel livestock has significantly regressed from 200,000 heads in the 1950's to 85,000 heads at the present time. Concentrated in the southern areas of the country, camel breeding is traditionally practiced in extensive form, mainly through using, the halophyte tracks. Its main present vocation is meat production. Preliminary studies conducted by the Arid Regions Institute of Medenine (Tunisia) have resulted in the perfecting of new techniques for the improvement of this species' productivity. Among these techniques, we quote the artificial nursing of young camels.
Séminaire sur la Digestion, la Nutrition et l'Alimentation du Dromadaire, 1988/02/27-1988/03/01, Ouargla (Algeria)